Cake Decoration Training as a Model for Strengthening Basic Cake Decoration Skills and an Introduction to Culinary Vocational Education for Vocational High School Students - Faisal Akbar Zaenal; Nurjannah Madjid; Intan Fauzia Amalia; Lily Dianafitry Hasan; Muhammad Anas (Pusat Studi Pembangunan dan Pemberdayaan, 2026)
This community service program was designed to strengthen basic cake decorating skills and to promote vocational culinary education among senior high school and vocational high school students through a practsice-based cake decoration workshop. Conducted by the Culinary Arts Study Program as part of an Open Campus initiative, the program sought to provide participants with an initial experience of applied learning that characterizes vocational education. The activity was implemented through preparation, instructional sessions, demonstration, hands-on practice, mentoring, and evaluation. Evaluation data were drawn from 63 participant responses collected after the activity. The findings revealed that 100% of participants considered the program beneficial and were satisfied with the overall activity, 90.5% felt more capable of decorating cakes after the training, 93.7% reported increased interest in the culinary field, and 98.4% expressed interest in joining advanced training. These findings indicate that practice-based cake decoration training is effective in providing early learning experiences, strengthening basic decorating skills, and introducing the applied nature of vocational culinary education to school students. Therefore, cake decoration training can serve as a relevant community service model for integrating basic skill development with the educational promotion of vocational culinary education.